Preparation method and application of modified oxygen-vacancy-rich 3D printing zero-valent iron catalyst
By depositing iron oxide gel on the surface of zero-valent iron powder and mixing it with triethanolamine, mechanical ball milling and 3D printing are carried out to form a modified oxygen-rich vacancies 3D printing zero-valent iron catalyst, which solves the problems of passivation, aggregation and recovery of zero-valent iron, and realizes the utilization of thermal energy and efficient degradation of organic pollutants.
Patent Information
- Application Number
- CN202411488153.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-03-07
AI Technical Summary
Zerovalent iron passivates rapidly on the surface, easily agglomerates, and is difficult to separate and recover from the degradation system, and the thermal energy generated by the 3D printing process cannot be utilized.
Iron oxide organic gel was deposited on the surface of zero-valent iron powder by sol-gel method, mixed with triethanolamine, and wet mechanical ball milling and 3D printing to form a modified oxygen-rich vacancies 3D printing zero-valent iron catalyst.
It effectively overcomes the problems of passivation, aggregation and recycling of zero-valent iron, and uses the thermal energy of the 3D printing process to prepare a modified catalyst with good catalytic properties, which can efficiently degrade organic pollutants in wastewater.
Smart Images

Figure CN119565685A_ABST
Abstract
Description
Technical field:
[0001] The present invention relates to the technical field of catalyst preparation, and in particular to a preparation method and application of a modified oxygen-rich vacancy 3D printed zero-valent iron catalyst. Background technology:
[0002] Currently, zero-valent iron is one of the most widely studied materials in the field of wastewater treatment and groundwater remediation because it is relatively environmentally friendly (compared to other zero-valent metals), low-cost (the fourth most abundant element in the earth's crust), and can treat difficult-to-biodegrade wastewater. However, the rapid surface passivation, easy agglomeration, and difficulty in separation and recovery from the degradation system of zero-valent iron are two major drawbacks that make it difficult to be widely used in various degradable water bodies.
[0003] With the rapid development of 3D printing technology (additive manufacturing technology), its application in the field of catalysts has gradually received attention. Through 3D printing technology, catalyst materials of any shape can be designed and manufactured according to demand. This method not only effectively reduces the waste of zero-valent iron materials, but also reduces the process cost of separating catalysts from water. However, the heat energy generated by the 3D printing process often dissipates directly as unusable energy. It is urgent to find a feasible method. Summary of the invention:
[0004] The purpose of the present invention is to provide a preparation method and application of a modified oxygen-rich vacancy 3D printed zero-valent iron catalyst, which solves the problems of rapid surface passivation, easy agglomeration and difficulty in separation and recovery from the degradation system of zero-valent iron, and also solves the problem that the heat energy generated in the 3D printing process cannot be utilized.
[0005] The present invention is achieved through the following technical solutions:
[0006] A method for preparing a modified oxygen-rich vacancy 3D printed zero-valent iron catalyst, the method comprising the following steps:
[0007] 1) dissolving iron oxide powder in a solution containing a triblock copolymer surfactant to react, and then adding zero-valent iron powder to form a sol and completely immersing it for a period of time (20-40 minutes), then pouring out the solution, and moving the powder in the solution to a hot air oven to completely dry the powder, thereby obtaining a modified zero-valent iron powder with iron oxide deposited on the surface of the zero-valent iron powder;
[0008] 2) Mixing the modified zero-valent iron powder obtained in step 1) with triethanolamine powder, adding the mixture into four ball mills of equal mass containing steel balls, wherein the mass ratio of steel balls to mixed powder is 3-5:1, and then adding ethanol for cooling and lubrication; transferring the obtained mixed powder into a planetary ball mill for wet mechanical ball milling at a speed of 380-420 rpm for 11-13 hours;
[0009] 3) drying the ball-milled powder obtained in step 2) in a hot air oven at 60-65° C. for 3-5 hours to obtain a completely dry powder, and transferring the powder to a mechanical shaker and passing it through a 200-mesh sieve to collect the powder;
[0010] 4) Pour the powder collected in step 3) into the powder cylinder, install the stainless steel substrate horizontally on the molding table and adjust the distance between the substrate and the powder scraper to basically fit, then close the printing chamber, and introduce argon gas so that the oxygen content in the chamber is less than 200ppm during the entire printing process; adjust the process parameters of the SLM2803D printer equipment: the laser power range is set to 160W~220W, the scanning speed range is set to 800~1000mm / s, the powder layer thickness is set to 50μm, the scanning spacing range is set to 60μm~120μm, and the scanning strategy adopts equidistant rotation of 75° in the X and Y directions to alternately scan, which can reduce the possibility of thermal stress causing material cracking;
[0011] 5) The finished product printed in step 4) is separated by a cutting water jet, moved to a beaker containing 72-78wt% ethanol solution and immersed in ultrasound for 12-18 minutes, then the ethanol solution and oil stains in the beaker are poured out, and the residual ethanol on the material is blown dry with nitrogen to obtain a modified oxygen-rich vacancy 3D printed zero-valent iron catalyst.
[0012] Preferably, the triblock copolymer surfactant comprises Pluronic P123 or F127 triblock copolymer surfactant.
[0013] In step 1), the mass ratio of iron oxide powder to zero-valent iron powder is 1:18-20.
[0014] In step 2), the mass ratio of the modified zero-valent iron powder to the triethanolamine powder is 55-65:1.
[0015] The present application first uses a sol-gel method to deposit an iron oxide organic gel on the surface of a zero-valent iron powder to form a modified zero-valent iron powder. A certain amount of triethanolamine is then mixed with the modified zero-valent iron powder, treated by wet ball milling and subsequently laser printed. Triethanolamine can reduce the electrostatic interaction and agglomeration between powder particles and promote uniform melting and solidification of the powder at high temperatures, and can also decompose to generate ammonia and carbon dioxide. In this process, the lattice oxygen on the surface of the zero-valent iron material is removed under a reducing and low-oxygen atmosphere, thereby forming abundant oxygen vacancies on the catalyst. Using this oxygen-vacancy-rich catalyst, the adsorption of hydrogen persulfate and the formation of its reaction complex can be significantly promoted, thereby efficiently degrading emerging pollutants in wastewater, such as sulfamethoxazole.
[0016] Therefore, the present invention also protects the use of the modified oxygen-rich vacancy 3D printed zero-valent iron catalyst obtained by the above-mentioned preparation method for removing organic pollutants in wastewater, comprising the following steps: adding potassium persulfate and the modified oxygen-rich vacancy 3D printed zero-valent iron catalyst to the wastewater containing organic pollutants.
[0017] Preferably, the concentration of the organic pollutants is 5 to 20 ppm.
[0018] The concentration of hydrogen persulfate is 0.1-2 mM.
[0019] The organic pollutants include sulfamethoxazole, carbamazepine, florfenicol, acetaminophen, etc.
[0020] The beneficial effects of the present invention are as follows:
[0021] 1) The present invention introduces a novel triblock copolymer surfactant Pluronic P123 or F127, and utilizes the gelation of the surfactant. In the process of preparing modified zero-valent iron powder by the sol-gel method, the triblock copolymer surfactant can promote the dispersion of iron oxide, change the structure of the zero-valent iron material, help provide more active sites for the material and facilitate further modification.
[0022] 2) The present invention introduces triethanolamine to reduce the electrostatic interaction and agglomeration between powder particles and promote the uniform melting and solidification of powder at high temperature. At the same time, the high temperature generated by mechanical ball milling and 3D printing will remove the residual organic matter and make the iron oxide more evenly distributed on the surface of zero-valent iron in the form of a microporous grid. At the same time, the high temperature environment will cause the triethanolamine powder to pyrolyze to produce ammonia and carbon dioxide to create a reducing and low-oxygen atmosphere, thereby causing the lattice oxygen on the surface of the material to lose and form abundant oxygen vacancies, which has good catalytic performance.
[0023] In summary, in the process of preparing the catalyst of the present invention, the gelation of the novel triblock copolymer surfactant is first utilized, and the iron oxide organic gel is deposited on the surface of the zero-valent iron powder by the sol-gel method to form a modified zero-valent iron powder, and then triethanolamine is mixed with the modified zero-valent iron powder, and the modified zero-valent iron powder is processed by wet ball milling, which utilizes the uniform dispersion of the powder particles of triethanolamine, and the three synergistic effects of the low-oxygen reducing atmosphere environment caused by mechanical ball milling and 3D printing, so that the lattice oxygen on the surface of the material is lost to form rich oxygen vacancies, and the material is continuously subjected to integrated physical and chemical modification, and finally a modified oxygen-rich vacancy 3D printing zero-valent iron catalyst is prepared, and the whole process is simple, without secondary pollution, reducing the waste of heat energy and saving costs. The catalyst prepared by the present invention not only effectively overcomes the defects of rapid passivation of the zero-valent iron surface, easy agglomeration and difficulty in separation and recovery from the degradation system, but also solves the problem that the heat energy generated by the 3D printing process cannot be utilized. Moreover, the prepared material can be used as a catalyst to utilize its abundant oxygen vacancies to adsorb and bind to hydrogen persulfate, thereby achieving efficient degradation of organic pollutants and having prospects for industrialization. Description of the drawings:
[0024] Figure 1 This is a scanning electron microscope image of the modified zero-valent iron powder obtained in Example 1.
[0025] Figure 2 This is a physical picture of the modified oxygen-rich vacancy 3D printed zero-valent iron catalyst obtained in Example 1.
[0026] Figure 3 This is the degradation data of sulfamethoxazole.
[0027] Figure 4 This is the degradation data of carbamazepine.
[0028] Figure 5 This is the oxygen vacancy EPR image of the modified oxygen-rich vacancy 3D printed zero-valent iron catalyst obtained in Example 1. Specific implementation method:
[0029] The following is a further description of the present invention, rather than a limitation of the present invention.
[0030] Example 1: Preparation method of modified oxygen-rich vacancy 3D printed zero-valent iron catalyst
[0031] The preparation method is as follows:
[0032] 1) 6 g of iron oxide powder was dissolved in a 1 mM copolymer surfactant (Pluronic P123) solution, and after a sol was formed, 112 g of zero-valent iron powder was completely immersed for 30 minutes, and then the solution in the beaker was poured out, and the powder was moved to a hot air oven to completely dry the powder to obtain a modified zero-valent iron powder with iron oxide deposited on the surface of the zero-valent iron powder; its scanning electron microscope image Figure 1 As shown, a layer of dense iron oxide gel is attached to the surface of the modified zero-valent iron powder of the present invention;
[0033] 2) Mix the modified zero-valent iron powder obtained in step 1) with 2 g of triethanolamine powder, repeat the above operation in four groups in parallel, and then add them into four ball mills of equal mass containing steel balls, wherein the mass ratio of steel balls to mixed powder is 4:1, and then add 3 ml of ethanol for cooling and lubrication;
[0034] 3) The mixed powder obtained in step 2) was transferred to a planetary ball mill for wet mechanical ball milling at a speed of 400 rpm for 12 hours;
[0035] 4) drying the powder obtained by ball milling in step 3) in a hot air oven for 3 hours to completely remove moisture, and then collecting the powder after passing it through a 200-mesh sieve using a mechanical shaker;
[0036] 5) Pour the powder collected in step 4) into the powder cylinder of the Hanbang SLM2803D printer equipment, install the stainless steel substrate horizontally on the molding table and adjust the distance between the substrate and the powder scraper to basically fit, then close the printing chamber, introduce argon gas so that the oxygen content in the chamber is less than 200ppm during the entire printing process, and adjust the process parameters: the laser power range is set to 160W~220W, the scanning speed range is set to 800~1000mm / s, the powder layer thickness is set to 50μm, the scanning spacing range is set to 60μm~120μm, and the scanning strategy adopts equidistant rotation of 75° in the X and Y directions for alternating scanning;
[0037] 6) The printed product in step 5) was separated by a cutting water jet, moved to a beaker containing 75wt% ethanol solution and immersed in ultrasound for 15 minutes, then the ethanol solution and oil stains in the beaker were poured out, and the residual ethanol on the material was blown dry with nitrogen to obtain a modified oxygen-rich vacancy 3D printed zero-valent iron catalyst product. Figure 2 As shown in FIG. 1 , the modified oxygen-rich vacancy 3D printed zero-valent iron catalyst prepared by the present invention has a certain geometric design shape, which is easier to recycle than conventional zero-valent iron powder and is not easily oxidized and deactivated. Figure 5 As shown, the modified oxygen-vacancy-rich 3D printed zero-valent iron catalyst prepared by the present invention has a strong oxygen vacancy signal.
[0038] Embodiment 2:
[0039] Refer to Example 1, except that F127 is used instead of Pluronic P123.
[0040] Example 3: Application of modified oxygen-rich vacancy 3D printed zero-valent iron catalyst in removing organic pollutants from wastewater
[0041] The modified oxygen-rich vacancy 3D printed zero-valent iron catalyst prepared in Example 1 was used to activate potassium persulfate to degrade wastewater containing sulfamethoxazole:
[0042] Sulfamethoxazole at a concentration of 10 ppm was added to a 500 ml beaker, wherein the reaction volume was 300 ml;
[0043] After adding potassium persulfate with a concentration of 200 μM and 3 g of modified oxygen-rich vacancy 3D-printed zero-valent iron catalyst, the timing was started. At 0, 0.5, 1, 2, 3, 5, 7, 10, and 15 min, 1 ml of the reaction solution was put into a 2 ml liquid phase vial, 20 μl of pure methanol was added to terminate the reaction, and then the solution was placed in a high performance liquid chromatograph to detect the residual concentration of pollutants.
[0044] Figure 3 As shown, the degradation performance of the modified oxygen-rich vacancy 3D printed zero-valent iron catalyst prepared by the present invention is very excellent, and the degradation rate can reach more than 99.9% within 15 minutes, which is conducive to the efficient degradation of sulfamethoxazole-containing wastewater and has the prospect of industrialization.
[0045] Example 4: Application of modified oxygen-rich vacancy 3D printed zero-valent iron catalyst in removing organic pollutants from wastewater
[0046] The modified oxygen-rich vacancy 3D printed zero-valent iron catalyst prepared in Example 2 was used to activate potassium persulfate to degrade wastewater containing carbamazepine.
[0047] Carbamazepine at a concentration of 10 ppm was added to a 500 ml beaker, where the reaction volume was 300 ml;
[0048] After adding potassium persulfate with a concentration of 200 μM and 3 g of modified oxygen-rich vacancy 3D-printed zero-valent iron catalyst, the timing was started. At 0, 0.5, 1, 2, 3, 5, 7, 10, and 15 min, 1 ml of the reaction solution was put into a 2 ml liquid phase vial, 20 μl of pure methanol was added to terminate the reaction, and then the solution was placed in a high performance liquid chromatograph to detect the residual concentration of pollutants.
[0049] The results are as follows Figure 4 shown.
Claims
1. A method for preparing a modified oxygen-rich vacancy 3D printed zero-valent iron catalyst, characterized in that: The method comprises the following steps: 1) dissolving iron oxide powder in a solution containing a triblock copolymer surfactant to react, and then adding zero-valent iron powder to form a sol and completely immersing it for 20-40 minutes, then pouring out the solution, and moving the powder in the solution to a hot air oven to completely dry the powder, thereby obtaining a modified zero-valent iron powder with iron oxide deposited on the surface of the zero-valent iron powder; 2) Mixing the modified zero-valent iron powder obtained in step 1) with triethanolamine powder, adding the mixture into four ball mills of equal mass containing steel balls, wherein the mass ratio of steel balls to mixed powder is 3-5:1, and then adding ethanol for cooling and lubrication; transferring the obtained mixed powder into a planetary ball mill for wet mechanical ball milling at a speed of 380-420 rpm for 11-13 hours; 3) drying the ball-milled powder obtained in step 2) in a hot air oven at 60-65° C. for 3-5 hours to obtain a completely dry powder, and transferring the powder to a mechanical shaker and passing it through a 200-mesh sieve to collect the powder; 4) Pour the powder collected in step 3) into the powder cylinder, install the stainless steel substrate horizontally on the molding table and adjust the distance between the substrate and the powder scraper to basically fit, then close the printing chamber, and introduce argon gas so that the oxygen content in the chamber is less than 200ppm during the entire printing process; adjust the process parameters of the SLM2803D printer equipment: the laser power range is set to 160W~220W, the scanning speed range is set to 800~1000mm / s, the powder layer thickness is set to 50μm, the scanning spacing range is set to 60μm~120μm, and the scanning strategy adopts equidistant rotation of 75° in the X and Y directions for alternating scanning; 5) The finished product printed in step 4) is separated by a cutting water jet, moved to a beaker containing 72-78wt% ethanol solution and immersed in ultrasound for 12-18 minutes, then the ethanol solution and oil stains in the beaker are poured out, and the residual ethanol on the material is blown dry with nitrogen to obtain a modified oxygen-rich vacancy 3D printed zero-valent iron catalyst.
2. The preparation method according to claim 1, characterized in that: Triblock copolymer surfactants include Pluronic P123 or F127 triblock copolymer surfactants.
3. The preparation method according to claim 1, characterized in that: In step 1), the mass ratio of iron oxide powder to zero-valent iron powder is 1:18-20.
4. The preparation method according to claim 1, characterized in that: In step 2), the mass ratio of the modified zero-valent iron powder to the triethanolamine powder is 55-65:
1.
5. The use of the modified oxygen-rich vacancy 3D printed zero-valent iron catalyst obtained by the preparation method of claim 1, characterized in that: Used to remove organic pollutants from wastewater.
6. The use according to claim 5, characterized in that: The following steps are involved: Potassium persulfate and modified oxygen-vacancy-rich 3D-printed zero-valent iron catalyst were added to wastewater containing organic pollutants.
7. The use according to claim 6, characterized in that: The concentration of the organic pollutants is 5 to 20 ppm.
8. The use according to claim 6, characterized in that: The concentration of hydrogen persulfate is 0.1-2 mM.
9. The use according to claim 6, characterized in that: The organic pollutants include sulfamethoxazole, carbamazepine, florfenicol, and acetaminophen.